OPTIMALISASI SUMBER DAYA ALAM DESA CILANGCANG MENUJU DESA WIRAUSAHAShifa Atiyatul Hasanah - Shifa (Jurnal Pengabdian Kepada Masyarakat, 2024)
The amount of waste produced by the community is already very large. In Kuningan Regency alone, it produces an average of 480 tons per day. The paradigm of waste management must be changed from collect-transport-dispose, to sort-collect-sell. One form of waste management that can be an economic benefit is a waste bank. The process of establishing a waste bank is 1. socialization, 2. technical training, 3. implementation, 4. monitoring and evaluation. We held a socialization of waste management through waste banks and pyrolysis equipment as a first step and stimulus for the community to implement. The community welcomed this socialization and wanted a follow-up after the socialization